The association between psoriasis and nonalcoholic fatty liver disease: Mediation analysis involving inflammatory biomarkers among U.S. adults - Xuewan Wang; Cunxiang Xie; Yutong Deng; Xuewen Ren; Yatong Li; Tangyunni Liu; Bo Hu; Huishang Feng; Yuanwen Li (PLoS ONE, 2026)
Background Psoriasis has been observed to be associated with an increased risk of nonalcoholic fatty liver disease (NAFLD). However, investigating novel mediators that influence the relationship between psoriasis and NAFLD is essential, given their complex interconnection. Currently, it remains unclear whether inflammatory biomarkers play a mediating role in this association. Methods Data from adults aged 20–60 years were obtained from the National Health and Nutrition Examination Survey (NHANES), which was conducted between 2003–2006 and 2009–2014. Logistic regression was used to analyze the association between psoriasis and NAFLD across three different models. Subgroup and interaction analyses were performed to explore potential nonlinear and independent relationships between psoriasis and NAFLD. Mediation analysis was conducted to determine whether the systemic immune-inflammation index (SII) and neutrophil-to-lymphocyte ratio (NLR), two inflammatory markers, mediate the relationship between psoriasis and NAFLD. Results A total of 9,439 participants were included in the study, of whom 3,961 had NAFLD, with a weighted prevalence rate of 41.96%. Compared with participants without psoriasis, those with psoriasis had a greater prevalence of NAFLD, reaching 50.99%. In all three models, psoriasis was positively associated with the risk of NAFLD, and a significant dose‒response relationship was observed (p < 0.05). Mediation analysis revealed that, in the adjusted models, Ln-SII and Ln-NLR statistically mediated the association between psoriasis and NAFLD, with percentages of 8.52% and 3.58%, respectively (p < 0.05). Conclusion Psoriasis is positively associated with the occurrence of NAFLD, and the SII and NLR play key mediating roles in the relationship between psoriasis and NAFLD.